Comparative analysis of the mitochondrial genomes of four Dendrobium species (Orchidaceae) reveals heterogeneity in structure, synteny, intercellular gene transfer, and RNA editing - Wang, Le; Liu, Xue; Wang, Yongde; Ming, Xingjia; Qi, Junsheng; Zhou, Yiquan (Frontiers in Plant Science, 2024)
The genus Dendrobium, part of the Orchidaceae family, encompasses species of significant medicinal, nutritional, and economic value. However, many Dendrobium species are threatened by environmental stresses, low seed germination rates, and overharvesting.Mitochondria generate the energy necessary for various plant life activities. Despite their importance, research on the mitochondrial genomes of Dendrobium species is currently limited. To address this gap, we performed a comprehensive genetic analysis of four Dendrobium species-D. flexicaule, D. nobile, D. officinale, and D. huoshanense-focusing on their mitochondrial and chloroplast genomes to elucidate their genetic architecture and support conservation efforts. We utilized advanced sequencing technologies, including Illumina for high-throughput sequencing and Nanopore for long-read sequencing capabilities.Our findings revealed the multichromosomal mitochondrial genome structures, with total lengths ranging from 596,506 bp to 772,523 bp. The mitochondrial genomes contained 265 functional genes, including 64-69 protein-coding genes, 23-28 tRNA genes, and 3 rRNA genes. We identified 647 simple sequence repeats (SSRs) and 352 tandem repeats, along with 440 instances of plastid-to-mitochondrial gene transfer. Additionally, we predicted 2,023 RNA editing sites within the mitochondrial protein-coding genes, predominantly characterized by cytosine-to-thymine transitions. Comparative analysis of mitochondrial DNA across the species highlighted 25 conserved genes, with evidence of positive selection in five genes: ccmFC, matR, mttB, rps2, and rps10. Phylogenetic assessments suggested a close sister relationship between D. nobile and D. huoshanense, and a similar proximity between D. officinale and D. flexicaule. This comprehensive genomic study provides a critical foundation for further exploration into the genetic mechanisms and biodiversity of Dendrobium species, contributing valuable insights for their conservation and sustainable utilization.